Role of the virtual reality simulator (ScanTrainer) as a multidisciplinary training tool in transvaginal ultrasound: A systematic review and narrative synthesis. Issue 3 (August 2019) - Almestehi, M.; Alomaim, W.; Rainford, L.; Stokes, D.; Stanton, M.; Moran, M.
Abstract: Objectives: This systematic review investigates the role of the ScanTrainer as a virtual reality training simulator and its impact on the scanning skills in transvaginal ultrasound of novice ultrasound practitioners. Key findings: After searching ten databases for studies incorporating the simulator as a part of the learning/training process, ten out of 684 studies met the eligibility criteria and were included in the review. The analysis of the textual findings using narrative synthesis approach resulted in four themes: Validation (assessment of the validity of the simulator), Learning (using the simulator as a learning tool), Perspectives (the perceptions of participants trained on the simulator), and Transferable skills (skills developed on the simulator can transfer to clinical practice). Conclusion: Although literature indicates that the simulator is valuable as a training/learning tool, there is insufficient evidence of measurable effects on clinical practice of simulator usage by different healthcare professions. Highlights: The simulator helps to increase scanning confidence. The VR-simulator is valuable as a self-learning tool. Learning aptitudes on the simulator may affect transvaginal scanning (TVS) competence. Further research is required to ascertain the impact of simulation-based training on the competence of the practitioner.